Strengthening the Mental Readiness of Petanque Athletes through Experiential Learning-Based Self-Talk Training at FIKK UNM - Nukhrawi Nawir; Tri Angriawan; Muflih Wahid Hamid; Syahrul Zaum; Muhammad Yusri (Jurnal Perjuangan dan Pengabdian Masyarakat : JPPM, 2026)
Petanque is a precision sport that requires high levels of concentration, emotional stability, and mental readiness to cope with competitive pressure. Student-athletes of Petanque at the Faculty of Sports Science and Health, Universitas Negeri Makassar, generally demonstrate adequate technical and physical abilities; however, mental skills training, particularly self-talk, has not been systematically integrated into their training programs. This community service activity aimed to strengthen athletes’ mental readiness through self-talk training based on experiential learning. The program employed a descriptive–participatory approach involving 28 student-athletes of Petanque at FIKK UNM. The training was conducted through three main stages: socialization, experiential games, and structured reflection. Data were collected qualitatively through direct observation and participants’ reflections. The results indicated that experiential learning–based self-talk training enhanced athletes’ awareness of their internal dialogue during sport activities. Athletes began to recognize the role of self-talk in maintaining focus, regulating emotions, and fostering positive team communication. Experiential activities enabled athletes to meaningfully connect self-talk concepts with real training and competition situations. This community service program demonstrates that self-talk training can serve as an applicable and relevant mental coaching strategy for student-athletes, particularly in precision sports such as petanque. The training model has the potential to be further developed and replicated as part of a holistic and sustainable athlete development program in higher education settings.